Penerapan Dasar Dan Tujuan Pendidikan Untuk Meningkatkan Kualitas Pembelajaran Di Sekolah - Anak Agung Sagung Oka Anggrena; Asti Melani Putri; Gusmaneli (CV. ITTC INDONESIA, 2024)
The foundations and objectives of education have an important role in improving the quality of learning in schools. Basic education is a crucial initial stage in a person's development, especially for students. This research aims to analyze the concept of basic implementation and educational objectives to improve the quality of learning in schools. This research uses library research by reviewing various literature and reviewing the development of research on the basics and goals of education. The basis of Islamic education is principles originating from Islamic teachings. With the aim of forming individuals who are balanced spiritually, intellectually, socially, and ready to face life in this world and the hereafter. The application of the basics and objectives of education to improve the quality of education in schools emphasizes the importance of a strong foundation in the education system. A clear educational foundation, such as moral and ethical values, as well as directed goals, can help create an effective learning environment.